Pengaruh Model Pembelajaran Problem Based Learning Terhadap Kemampuan Komunikasi Matematis Siswa - Madita, Parina; Zulhendri; Astuti (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2025)
This study is based on the low ability of students in mathematical communication in class X of SMA Negeri 1 Kuok, which can be seen from their learning outcomes. The purpose of this study was to evaluate whether there was an impact of the implementation of the problem-based cooperative learning model on students' mathematical communication skills in class X of SMA Negeri 1 Kuok. This type of research is a quasi-experimental study with a sampling technique using simple random sampling. The population studied were students of class X of SMA Negeri 1 Kuok for the 2024/2025 Academic Year which were divided into two classes. The selected sample was class X.1 as the control group and class X.2 as the experimental group. The instruments used in this study included observation sheets and test questions to measure mathematical communication skills. The data analysis method applied was the Independent Sample T-Test with the support of SPSS 25 software. The average Pre-test score of students' mathematical communication skills in the experimental class was 40.00, while the control class reached 47.39. The average Post-test score of students' mathematical communication skills in the experimental class increased to 72.17, while the average control class was 61.96. Thus, it can be concluded that there is an influence of the Problem Based Learning learning model on students' mathematical communication skills in class X of SMA Negeri 1 Kuok. This can be proven through the Independent Sample T-Test which shows a sig (2-tailed) value of 0.000 which is smaller than 0.05, so H0 is rejected and Ha is accepted.